2017
DOI: 10.1007/s11469-017-9822-3
|View full text |Cite
|
Sign up to set email alerts
|

Why Do You Drink Caffeine? The Development of the Motives for Caffeine Consumption Questionnaire (MCCQ) and Its Relationship with Gender, Age and the Types of Caffeinated Beverages

Abstract: Caffeine is the most popular psychoactive substance that is consumed worldwide. As motives influence behavior, investigation of the motivational background of caffeine consumption should help provide a better understanding of the popularity of caffeinated products. The present study aimed (i) to explore and operationalize the motives of caffeine consumption and (ii) to reveal possible differences in the motives regarding gender, age and the type of caffeinated products consumed. Motives for caffeine consumptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 64 publications
4
43
0
2
Order By: Relevance
“…The results of this study indicated that the motivations for caffeinated beverage consumption were sensory effects, alertness, social factors, health benefits, mood, and habit, similar to the results of a previous study [30]. Interestingly, the motivations for the consumption of each caffeinated beverage were different.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…The results of this study indicated that the motivations for caffeinated beverage consumption were sensory effects, alertness, social factors, health benefits, mood, and habit, similar to the results of a previous study [30]. Interestingly, the motivations for the consumption of each caffeinated beverage were different.…”
Section: Discussionsupporting
confidence: 83%
“…The participants were asked about their motivations for consuming caffeinated beverages and the questions were adapted from previous studies [30,31]. The questions were presented with a 5-point Likert scale (1: never~5: always).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ebenfalls wurde eine Verbesserung der Stimmung von einigen Nutzern nach akuter Anwendung von Koffein berichtet [137,[155][156][157]. Im Rahmen von Befragungen wurde gefunden, dass viele Personen, die regelmäßig Koffein konsumieren (in Form von koffeinhaltigen Getränken), dabei das Ziel einer Leistungssteigerung, verlängerter Wachzeit oder Stimmungsverbesserung verfolgen [158,159]. In Placebo-kontrollierten Untersuchungen konnte gezeigt werden, dass vor allem männliche Individuen Getränke mit Koffein eher mehr mochten ("liking behavior") und mehr von den koffeinhaltigen Getränken verlangten [160].…”
Section: Objektive Und Subjektive Effekte Von Koffeinunclassified